(untitled) (Development Service Industry Management, 2024)
Trade is an important component of the theoretical sector of the economy — the service sector. It has an important place in the economy of Ukraine in terms of filling the state budget and extra-budgetary funds, meeting the needs of the population in workplaces, goods and services. Special attention to retail trade, which is able to quickly respond to changes in the needs and preferences of consumers, as well as being as close and accessible as possible to places of work and residence is paid. The results of scientific research by well-known domestic economists regarding the features, trends and regularities of the formation of retail turnover of domestic enterprises in the period of economic instability, internal and external threats are highlighted. The need to pay more attention to the study of retail development issues in the near and more distant perspective, taking into account world trends and experience, was emphasized, since Ukraine is actively integrating into the European economic space. The purpose of the study was to identify the main global trends and directions of development of retail trade, which will determine the vector of economic development of Ukraine and other countries of the world in the coming decades in the context of economic recovery and achieving the goals of sustainable development. The positive trend of increasing the volume of retail turnover in Ukraine in the current year has been analyzed. Global trends in the development of retail trade until 2050 are summarized. Expected trends in the transformation of global retail trade are characterized, which in the next five years will affect the marketing strategies of domestic enterprises: the transformation of traditional shopping into a part of the buyer’s environment with a seamless shopping experience; increase in the value of partnership relations as loyalty to brands decreases; recognition of generation Z as the new driving force of shopping; growing need of conscious consumers for increased attention from sellers and reliable protection of personal data.